Spatio-Temporal Variation of Soil Phosphorus and Its Implications for Future Pomelo Orcharding System Management: A Model Prediction From Southeast China From 1985–2100 - Yan, Xiaojun; Li, Guohua; Zhang, Weiqiang; Muneer, Muhammad Atif; Yu, Wenjia; Ma, Changcheng; Wu, Liangquan (Frontiers in Environmental Science, 2022)
Phosphorus (P) is a non-renewable source that is required in large amounts to maintain crop growth and development. The excessive P fertilizer contributes to the accumulation of P in the soil and results in increased soil Olsen P and total P. However, the spatio-temporal variation of soil P remains unclear in pomelo orchard systems. Therefore, this study aimed to assess the temporal and spatial variation of soil P in pomelo orchards and prediction of future P pool based on the dynamic P pool simulator (DPPS) model. The results showed that from 1985 to 2015, the annual P surplus ranged from 70.19 to 449.12 kg ha−1 with an average of 282.23 kg ha−1 yr−1, and the concentration of Olsen P and total P in topsoil increased significantly by 41 and 24-fold, respectively. Similarly, Olsen P and total P pools also increased from 7 to 297 kg ha−1 and 105 to 2675 kg ha−1, respectively. The Olsen P concentration and P pool in the natural forest were not significantly different at 0–200 cm soil depth, while in 20-year-old pomelo orchard, these were affected at 0–60 cm soil depth. The total P pool in the natural forest was not significantly different at 0–200 cm soil depth, while decreased from 3450 kg ha−1 to 178 kg ha−1 in 20-year-old pomelo orchard. Scenario analyses from 1985 to 2100 indicated that P application rate at 28.14 kg ha−1 could also maintain pomelo production at its optimum level, and the P application at 0 kg ha−1 could be adopted for decreasing the legacy P. These findings provide the synthesized novel insight for understanding the soil P status and its management in pomelo orchard systems of China.